Introduction to adaptive arrays - Monzingo, Robert A. 1938-; Haupt, Randy L.; Miller, Thomas W. (SciTech Publishing, 2011)
The following topics are dealt with in this book: adaptive array fundamental principles: system uses, system elements, basic concepts, and optimum array processing; and adaptive algorithms.